The effectiveness of logotherapy in powerlessness in cancer patients undergoing chemotherapy - Zulfitrah Romadiansyah; Sri Wahyuni; Nurul Huda; Wan Nishfa Dewi; Erika Erika (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Cancer patients undergoing chemotherapy often have physical and psychological impacts. The psychological impact caused is powerlessness. The problem of powerlessness must be handled well because otherwise it can develop into despair and the risk of suicide. The intervention to overcome powerlessness is logotherapy. Logotherapy is a type of psychotherapy that aims to help patients find the meaning of life. Purpose: To determine the effectiveness of logotherapy in cancer patients who experience powerlessness during chemotherapy. Method: A quantitative with a quasi-experimental nonequivalent control design. The total sample was 56 participants and used a nonprobability sampling technique with purposive sampling type. The instrument used was the Powerlessness Assessment Tool for Adult Patients Questionnaire. This research uses statistical tests are the Wilcoxon Sign Rank Test, Mann-Withney U Test, and Independent Sample T Test. Results: Statistical test results showed that there was a significant effect of logotherapy on the powerlessness of cancer patients undergoing chemotherapy with p value (0.000) < alpha (0.05). Conclusion: Logotherapy is effective in overcoming the problem of powerlessness in cancer patients undergoing chemotherapy.